EXPLORATION OF THE RELATIONSHIP BETWEEN CHILDHOOD ABUSE & PSYCHOSIS: A CRITICAL LITERATURE REVIEW - Manning, Claire (2008)
Background Trauma has long been recognised as a potential cause for a range of non-psychotic mental health problems in adulthood. However, only in recent years has the relationship between childhood abuse and psychosis in adulthood begun to be investigated. Aim This study aims to explore and critically review the literature addressing the relationship between childhood abuse and psychosis in adulthood. Clinical implications for mental health nurses will be discussed in order to relate the study to mental health nursing practice. Method Studies, theories and concepts relevant to this topic area were critically reviewed in order to gain a condensed overview of the existing literature base. Various sources were used to identify the relevant literature, including electronic databases, as well as manually searching journals, books, reference lists and websites. Results Histories of childhood abuse are often present in those individuals who experience psychosis in adulthood, suggesting a causal relationship may exist.